Plants, people and long‐term ecological monitoring in the tropics. Issue 3 (27th April 2021) - Pennington, R. Toby; Baker, Timothy R.
Abstract : This special issue focuses on long‐term ecological monitoring in the tropics, with a particular focus, appropriate to Plants, People, Planet, on what it can offer both to local people and decision makers in tropical countries. Two of the contributed papers emphasise the role that long‐term, permanent monitoring plots can play in bringing together researchers, policymakers and communities, based on examples from Peru and Colombia (Baker et al., Norden et al.). The articles also highlight new plot‐based methods for monitoring the neglected tropical dry biomes of savannas and dry forests (The SEOSAW Partnership; Moonlight et al.) and new methods for field‐based monitoring of habitat degradation (Ahrends et al.) and the distribution of large trees (Harris et al.). Overall, the issue demonstrates that sustainable management of tropical environments requires long‐term, ground‐based monitoring that engages with the communities and institutions that manage these landscapes.